Temporal Variation of the Current Sheet Inductance from PACO Plasma Focus Device - Barbaglia, Mario Oscar (2016)
The temporal variation of the current sheet (CS) inductance in a plasma focus device can be calculated using the current derivative and the voltage signal acquired on the anode electrode, which are very common measurements in this type of device. The value of that inductance contains important information about the discharge performed including the CS lift-off from the insulator, voltage between the pinch extremes, maximum energy of the X-ray, energy delivered to the pinch and information about the actuating fusion mechanisms if the filling pressure is deuterium. This work discusses the values of the CS inductance extracted from several discharges of the Plasma Auto Confinado (PACO) plasma focus, installed in the National University of the Center of Buenos Aires—Argentina (2 kJ total energy, capacitor bank of 4 μF charged to 31 kV and a maximum current of 250 kA).